Directing Multicellular Organization by Varying the Aspect Ratio of Soft Hydrogel Microwells. Issue 17 (17th April 2022) - Pahapale, Gayatri J.; Tao, Jiaxiang; Nikolic, Milos; Gao, Sammy; Scarcelli, Giuliano; Sun, Sean X.; Romer, Lewis H.; Gracias, David H.
Abstract: Multicellular organization with precise spatial definition is essential to various biological processes, including morphogenesis, development, and healing in vascular and other tissues. Gradients and patterns of chemoattractants are well‐described guides of multicellular organization, but the influences of 3D geometry of soft hydrogels are less well defined. Here, the discovery of a new mode of endothelial cell self‐organization guided by combinatorial effects of stiffness and geometry, independent of protein or chemical patterning, is described. Endothelial cells in 2 kPa microwells are found to be ≈30 times more likely to migrate to the edge to organize in ring‐like patterns than in stiff 35 kPa microwells. This organization is independent of curvature and significantly more pronounced in 2 kPa microwells with aspect ratio (perimeter/depth) < 25. Physical factors of cells and substrates that drive this behavior are systematically investigated and a mathematical model that explains the organization by balancing the dynamic interaction between tangential cytoskeletal tension, cell–cell, and cell–substrate adhesion is presented. These findings demonstrate the importance of combinatorial effects of geometry and stiffness in complex cellular organization that can be leveraged to facilitate the engineering of bionics and integrated model organoid systems with customized nutrient vascular networks. Abstract : A mode of cell organization in response to three‐dimensional geometry on soft substrates is presented. Cell organization is controlled by tuning the aspect ratio of the geometry, independent of chemical patterning and curvature. Cell and physical parameters regulating this cell organization are elucidated, used to guide cell organization in customized patterns, and investigate fundamental questions relevant to tissue development.